PROMOTING LOCAL ISSUES BASED TEACHING AND RESEARCH IN A GLOBALIZED WORLD – A CASE STUDY OF A LARGE PRIVATE UNIVERSITY IN PAKISTAN - Khan, Atif (European Scientific Journal, ESJ, 2015)
In 2015 a small study was conducted at one of the largest private universities in Pakistan. It confirmed earlier observations about the disconnect between foreign curriculum being taught in the Masters and Bachelors programs at the university and the issues facing employers in the country. A specific research exercise was then planned to interview 50 faculty members and understand the causes behind reliance on foreign books, the minimal use of local case studies as well as examples and lack of on-going exposure of the faculty to the hiring organizations in Pakistan. The study yielded interesting causes behind the disconnect including the mass commercialization of education, the need for globalizing content, easier access to foreign over local content, overloading courses on faculty, faults in matching teachers and courses due to large-scale intake of students, poor human resource management, performance appraisal and remuneration policies as well as the inattentive attitude of the university towards research and the professional development of faculty members. The impact of this disconnect on the learning experiences and achievements of students is discussed and recommendations are provided for developing systematic and strategic professional development programs for promoting local issues based teaching and research while maintaining a globalized outlook.